Design and Characterisation of Personal Hygiene Gels Containing a Gypsophila Trichotoma Extract and Xanthium Strumarium Essential Oil - Aleksandar Shkondrov; Denitsa Momekova; Maya Margaritova Zaharieva; Hristo Najdenski; Ekaterina Kozuharova; Ilina Krasteva (Cosmetics)
The aim was to develop a series of handwashing gels containing a standardised extract of the aerial part of Gypsophila trichotoma as well as an essential oil from Xanthium strumarium fruits. The saponins present in the extract are a suitable alternative to synthetic sulphate surfactants and have better skin tolerance, and with the addition of essential oil, a higher antibacterial activity of the gels thus developed is achieved. The elaborated gels were characterised by good spreadability and a pH close to the physiological for healthy skin (pH 5.5), which is a prerequisite for improved skin tolerability. The dynamic rheological studies showed that the extract fraction increase was not associated with gel viscosity change, and it was only a function of the gelling agent concentration. The gels’ foam-forming ability increased with the increasing extract concentrations. The comparative evaluation of the antibacterial activity of elaborated gels vs. plain gel based on coco glucoside against a panel of selected pathogens demonstrated that the newly developed formulations have superior antibacterial effects. Based on the good technological characteristics and the results of antimicrobial testing of the washing gels thus developed, it can be concluded that they are promising candidates as personal hygiene products.